Consciousness Development in Rastafari: A Perspective from the Psychology of Religion - Stokke, Christian (Anthropology of consciousness, 2021)
This paper explores a Rastafari perspective on consciousness development and relates this to developmental stage theories of consciousness evolution from the psychology of religion. The empirical material is from fieldwork on an online Rastafari community with global reach but run by a group based in Trinidad. The people on this particular forum align with the “spiritual, but not religious” trend in contemporary religiosity, which means they are more focused on interior questions of consciousness raising than on religious externals. This paper interprets empirical material from the dialogues on this forum in light of Rastafari theorist Dennis Forsythe. It compares this Rastafari theory of stages of consciousness, symbolized by the animals Anancy, lion, and lamb, to developmental theories of consciousness evolution. These are drawn from psychology and the psychology of religion (Maslow 1970; Kohlberg 1981; Fowler 1981; Gilligan 1982; Wilber 2007), which focus on preconventional, traditional, modern, pluralist, and integral stages.